PENGARUH JUMLAH PASIEN TERHADAP JUMLAH KOLONI BAKTERI PADA MEMBRAN DAN BELL STETOSKOP DI SALAH SATU RUMAH SAKIT KOTA MALANG - Nadira Iswarini Hapsari Adi (Jurnal Kedokteran Komunitas, 2018)
Introduction: Nosocomial or hospital acquired infection is an infection occurred while patient were hospitalized or when receiving medical care. Health care workers can transmit pathogens causing the infection through medical devices, especially stethoscopes. This study aims to determine whether the number of patients affects the number of bacterial colonies found in membrane and bell stethoscope.Methodology : This research is in-vitro study using post-test only observastional analytical research design by comparing the number of bacterial colonies on the membrane and bell stethoscope with the number of patients. Bacteria are inoculated on Nutrient agar media, Blood agar plate, and MacConkey to determine the number of colonies and bacterial properties in reducing lactose and lysis of blood. The bacteria were inoculated for 24 hours before counting the number of coloniesResult: The number of bacterial colonies on the stethoscope membrane in the VIP room compared to the stethoscope membrane class III did not show significant results(P>0.05). Between the number of bacterial colonies in the bell stethoscope in the VIP room compared to bells in class III rooms also did not get significant results(P>0.05). There was no significant difference(P>0.05) between The number of bacterial colonies in the membrane compared with bells in the VIP room and class III. The number of patients did not correlate with the number of bacterial colonies on the membrane(P>0.05) while the number of patients found a correlation(P<0.05) with the number of bacterial colonies on the bell stethoscopeConclusion: There is a correlation between the number of patients with bacterial colonies at the bell stethoscope while there is no correlation between the number of patients with bacterial colonies on the membrane